2010
DOI: 10.1080/17470211003602420
|View full text |Cite
|
Sign up to set email alerts
|

Fear selectively modulates visual mental imagery and visual perception

Abstract: Emotions have been shown to modulate low-level visual processing of simple stimuli. In this study, we investigate whether emotions only modulate processing of visual representations created from direct visual inputs or whether they also modulate representations that underlie visual mental images. Our results demonstrate that when participants visualize or look at the global shape of written words (low-spatial-frequency visual information), the prior brief presentation of fearful faces enhances processing, wher… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
14
0

Year Published

2013
2013
2018
2018

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 21 publications
(16 citation statements)
references
References 19 publications
(27 reference statements)
2
14
0
Order By: Relevance
“…As can be seen in our contrast sensitivity function (Figure 2C), emotional arousal increases contrast sensitivity at relatively low spatial frequency ranges but reduces it at high ranges. Thus, the current findings offers further support not only for Phelps et al's (2006) study that showed emotion-induced enhancement in contrast perception with (fixed) low spatial frequency target (2 cpd) across the experiment, but also for Bocanegra and Zeelenberg's (2009b) study that found emotion enhanced sensitivity for low spatial frequency stimuli but impaired it for high spatial frequency stimuli (see also, Borst & Kosslyn, 2010; Song & Keil, 2013). …”
Section: Discussionsupporting
confidence: 82%
“…As can be seen in our contrast sensitivity function (Figure 2C), emotional arousal increases contrast sensitivity at relatively low spatial frequency ranges but reduces it at high ranges. Thus, the current findings offers further support not only for Phelps et al's (2006) study that showed emotion-induced enhancement in contrast perception with (fixed) low spatial frequency target (2 cpd) across the experiment, but also for Bocanegra and Zeelenberg's (2009b) study that found emotion enhanced sensitivity for low spatial frequency stimuli but impaired it for high spatial frequency stimuli (see also, Borst & Kosslyn, 2010; Song & Keil, 2013). …”
Section: Discussionsupporting
confidence: 82%
“…Although audible and haptic cues are referenced in text, no auditory or haptic stimuli are experienced. That said, TPL may evoke imagery of represented gestures, sounds, or facial expressions, which can make the message more concrete and realistic (Borst & Kosslyn, 2010).…”
Section: In‐person Nonverbal Communication and Behaviormentioning
confidence: 99%
“…On one side, some patients report difficulties when asked to imagine the feared situation; furthermore, emotions have been shown to modulate visual imagery and perception [10], impairing visualization of detailed scenes. On the other side in vivo exposure is not fully under the control of the therapist and requires a high effort in terms of money and time expenditure.…”
Section: Introductionmentioning
confidence: 99%